HUMAN RESOURCE MANAGEMENT IN THE TOURISM INDUSTRY MALAYSIA DURING POST COVID-19 PANDEMIC - Chin, Tay Lee; Chee, Tay Lee (International Journal of Application on Economics and Business, 2024)
Human resource management (HRM) appears to have a favourable impact on organisational performance. However, HRM in the tourism business is defined by ad hoc and short-term initiatives, and as a result, the industry typically has a negative image of employment practises and circumstances. Thus, this paper looked at how the role of HRM in Malaysian hotels changed before, during, and after the COVID-19 outbreak. The main ideas for the investigation of HRM in both crises and the tourist and hospitality industry are introduced in a theoretical review. Theoretical review presents HRM has a variety of good outcomes, including improved corporate and financial performance, increased employee motivation, and lower voluntary staff turnover. It was discovered that the tourism business issues with a negative image of employment practises and circumstances when it comes to HRM. Despite the fact that employees represent the sector, HR practises are ad hoc. In recent years, the tourism business has undergone changes, but these changes have been happened slowly. Low salaries, unsocial hours and shift tasks, poor or non-existent career structures and restricted prospects for development, informal recruitment practises, or high levels of staff turnover, according to the literature, HRM faces a variety of challenges in the business.